Antibacterial Effect Essential oil and Extracts of Medicinal Plant on the Causal Agents of Bacterial Canker and Leaf Spot on the Stone Fruit Tree - H Mahmoudi; K Rahnama; MA Arabkhani (Institue of Medicinal Plants, ACECR, 2010)
Background: Bacterial canker and leaf spot caused by Pseudomonas syringae pv. syringae (Pss) and Xanthomonas arboricola pv. pruni (Xap) are one of important disease stone fruit tree. Objective: We studied antibacterial activities of fourteen essential oil and four plant extracts on these bacteria. Methods: The assay was carried in Petri dishes containing nutrient agar medium in which there was a well in the center of each Petri dish. These wells filled by 12µl aliquots of the essential oil and extracts. After 48h inoculation of bacteria suspension on the surface medium growth inhibition on zone around the wells was measured. Data analyzed by SAS software. Results: Results showed among essential oil and of plant in inhibition of growth bacteria was significantly difference (p<0.00001). Essential oil of Mentha piperita, Cuminum cyminum, Ziziphora tenuior, Tarchyspermum copticum and Salvia officinalis whit 6.3, 6.17, 5.77, 5.57, 4.77 cm have almost inhabitation on Xap respectively. Essential oil of Achillea millefolium, Coriandrum sativum, Heracleum persicum and Salvia officinalis extracts showed lowest antibacterial activities. Azadirachta indica extracts showed highest and Ferula assa-foetida and Thymus vulgaris extracts have any antibacterial effect. Essential oil of Thymus vulgaris, Tarchyspermum copticum, Cuminum cyminum and Mentha piperita, have almost inhibition on Pss respectively. Essential oil of Ziziphora tenuior, Coriandrum sativum and Rosmarinus officinalis have medium and Achillea millefolium, Coriandrum sativum and Artemisia annua have lowest activities on Pss and Salvia officinalis, Ferula assa-foetida have any effect on Pss. Conclusion: This study revealed that essential oils of these plants have high antibacterial activities and can be use for control plant disease.